Trends in cause-specific mortality among children aged 5–14 years from 2005 to 2016 in India, China, Brazil, and Mexico: an analysis of nationally representative mortality studies. Issue 10176 (16th March 2019) - Fadel, Shaza A; Boschi-Pinto, Cynthia; Yu, Shicheng; Reynales-Shigematsu, Luz Myriam; Menon, Geetha R; Newcombe, Leslie; Strong, Kathleen L; Wang, Qiqi; Jha, Prabhat
Summary: Background: With global survival increasing for children younger than 5 years of age, attention is required to reduce the approximately 1 million deaths of children aged 5–14 years occurring every year. Causes of death at these ages remain poorly documented. We aimed to explore trends in mortality by causes of death in India, China, Brazil, and Mexico, which are home to about 40% of the world's children aged 5–14 years and experience more than 200 000 deaths annually at these ages. Methods: We examined data on 244 401 deaths in children aged 5–14 years from four nationally representative data sources that obtained direct distributions of causes of death: the Indian Million Death Study, the Chinese Disease Surveillance Points, mortality data from the Mexican Instituto Nacional de Estadística y Geografía, and mortality data from the Brazilian Institute of Geography and Statistics. We present data on 12 main disease groups in all countries, with breakdown by communicable and nutritional diseases, non-communicable diseases, injuries, and ill-defined causes. To calculate age-specific and sex-specific death rates for each cause, we applied the national cause of death distribution to the UN mortality envelopes for 2005–16 for each country. Findings: Unlike Brazil, China, and Mexico, communicable diseases still account for nearly half of deaths in India in children aged 5–14 years (73 920 [46·1%] of 160 330 estimated deaths in 2016). In 2016, India had the highest death rates in nearly every category, including from communicable diseases. Fast declines among girls in communicable disease mortality narrowed the gap by 2016 with boys in India (32·6 deaths per 100 000 girls vs 26·2 per 100 000 boys) and China (1·7 vs 1·5). In China, injuries accounted for the greatest proportions of deaths (20 970 [53·2%] of 39 430 estimated deaths, in which drowning was a leading cause). The homicide death rate at ages 10–14 years was higher for boys than for girls in Brazil, increasing annually by an average of 0·7% (0·3–1·1). In India and China, the suicide death rates were higher for girls than for boys at ages 10–14 years. By contrast, in Mexico it was higher for boys than for girls, increasing annually by an average of 2·8% (2·0–3·6). Deaths from transport injuries, drowning, and cancer are common in all four countries, with transport accidents among the top three causes of death for both sexes in all countries, except for Indian girls, and cancer in the top three causes for both sexes in Mexico, Brazil, and China. Interpretation: Most of the deaths that occurred between 2005 and 2016 in children aged 5–14 years in India, China, Brazil, and Mexico arose from preventable or treatable conditions. This age group is important for extending some of the global disease-specific targets developed for children younger than 5 years of age. Interventions to control non-communicable diseases and injuries and to strengthen cause of death reporting systems are also required. Funding: WHO and the University of Toronto Connaught Global Challenge.